Performance comparison of the Java and Kotlin programming languages based on an auto-scroller mobile game - Piotr Gajek; Małgorzata Plechawska-Wójcik (Journal of Computer Sciences Institute)
The article contains a performance comparison of two mobile applications, developed in the Java and Kotlin programming languages respectively. The applications took the form of an auto-scroller game and shared their graphics assets. The aim of the work was to confirm or reject the hypothesis: Java is slightly more efficient than Kotlin in the presented context. The subject of comparison was the consumption of CPU, RAM and the device’s battery resources. The mentioned metrics were obtained using the Android Profiler tool. The study was conducted using two mobile devices. The results confirm the research hypothesis.